Algorithm for constructing and interpreting the graph “Business Cycle Tracer” - L. О. Yaschenko; О. M. Motuzka (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
Business cycle is a short-term or medium-term economic cycle involving sequential periodical moves of economy through the four phases: growth (boom), recession (crisis), depression, recovery.The objective of the article is to present the algorithm for constructing the graph “Business Cycle Tracer”, determine the periods of phases of business cycle using the business climate indicator for the Ukrainian economy, adjusted by Hodrick — Prescott Filter, and analyze the key macroeconomic indicators for each phase.The business climate indicator allows for constructing the graph “Business Cycle Tracer ”. Its algorithm includes the following phases:Adjust business climate indicator, to determine business cycles by use of Hodrick—Prescott Filter.Compute absolute growth for the business climate indicator adjusted by use of Hodrick-Prescott Filter (previous level is deducted from current level).Construct “Business Cycle Tracer” in Excel.Determine turning points and phases of business cycle.The graph “Business Cycle Tracer” constructed for Ukraine shows the data for the period from III quarter 2002 till II quarter 2016, with estimates for II quarter 2015 — II quarter 2016 being predicted ones.As follows from the analysis of the graph, from IV quarter 20023 till II quarter 2004, from II quarter 2006 till III quarter 2007, from IV quarter 2010 till I quarter 2011, from III quarter 2012 till II quarter 2013, the estimates of the business climate indicator adjusted by Hodrick — Prescott Filter were located in I quadrant, which means that the Ukrainian economy was at the growth (boom) phase in these periods.In III quarter 2002, from III quarter 2004 till I quarter 2006, from IV quarter 2007 till III quarter 2008, in II quarter 2011, from III quarter till IV quarter 2013, the estimates the business climate indicator adjusted by Hodrick — Prescott Filter were located in II quadrant, which means that the Ukrainian economy was at the recession (crisis) phase in these periods.From IV quarter 2008 till III quarter 2009, from III quarter 2011 till I quarter 2012, from I quarter 2014 till III quarter 2015, the estimates the business climate indicator adjusted by Hodrick - Prescott Filter were located in III quadrant, which means that the Ukrainian economy was at the depression phase in these periods.From IVquarter 2009 till III quarter 2010, in II quarter 2012, from IVquarter 2015 till II quarter 2016, the estimates the business climate indicator adjusted by Hodrick - Prescott Filter were located in IV quadrant, which means that the Ukrainian economy was at the recovery phase in these periods.Basically, analysis of the graph shows that the phase of growth (boom) was the longest one in the Ukrainian economy in the period under study. However, since I quarter 2014 the Ukrainian economy has been in the depression phase, although, according to prediction, its recovery phase will occur and last from IV quarter 2015 till II quarter 2016. 7 turning points can be identified on “Business Cycle Tracer”. Peaks: II quarter 2004, III quarter 2007, I quarter 2011, and II quarter 2013. Troughs: III quarter 2009, I quarter 2012, and III quarter 2015. The results allow for the conclusion that the economy is hit stronger at the depression phase than at the crisis phase; foreign investment is required for getting out of the depression phase. At times of the notorious financial and economic crisis lasting from the end of2008 till the end of2009, the Ukrainian economy was at the depression phase, and this phase was predictable.